The Principle of Indefinite Noun Repetition (Isim Nakirah) in Quranic Exegesis: : A Linguistic Analysis of Quranic Verses in Books of Tafsir - Muchammad Akrom (Universitas Islam Negeri Madura, 2026)
This study is driven by the question of how the rule of repetition of indefinite nouns (isim nakirah) is applied in the interpretation of several Qur’anic verses. It is grounded in the diversity of interpretations found in tafsir literature regarding the use of this rule, as well as the varied understandings of the function of such repetitions. Theoretically, this research positions itself as an evaluation of the applicability and relevance of linguistic principles in interpreting Qur’anic verses. This study employs a qualitative method through library research, examining various primary tafsir sources to identify patterns of acceptance or rejection of this rule. The findings reveal that the application of the repetition of indefinite nouns is interpreted in diverse ways in Qur’anic exegesis. Some exegetes interpret it as emphasis and reinforcement (takrĭr wa ta’kĭd), such as al-Zamakhsharĭ, Quraish Shihab, and the Indonesian Ministry of Religious Affairs’ Tafsir, while others, such as Ibn Kathĭr and al-Suyūṭĭ, apply a differentiation of meaning based on the aghlabiyyah principle, although certain scholars like al-Zamakhsharĭ and Quraish Shihab also employ this principle in other Qur’anic contexts. This diversity of interpretation is evident in the varying meanings attributed to terms such as yusrā, ḍa‘f, quwwah, and a‘mā. This study highlights the importance of a focused examination of the repetition of indefinite nouns by demonstrating the unique variations in the application of linguistic rules among exegetes, thereby raising significant issues regarding the flexibility and dynamic nature of linguistic methodologies in Qur’anic interpretation, a topic that has often been treated only in general terms.